Integration of fruit in the formulation of feed for Oreochromis niloticus breeding in the region of Vakinankaratra, Madagascar - Rindra, Rabarison; Ravelomanantsoa Ramanambe Nicole; Rabeharitsara Andry Tahina; Rakotomamonjy Pierre; Razafimahefa Mirana Verohanitra; Koto-te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina Baholy (Britain International for Academic Research (BIAR) Publisher, 2024)
To promote the nutrition of tilapia in farming, four foods were created using traditional raw materials and containing different quantities of locally produced banana flour. These foods, which contain 36% crude proteins and 8% lipids, were tested on tilapia fry with an initial weight of 8 grams. After 50 days of the experiment, the final weights of the fish fluctuated between 33.28 grams and 41.4 grams, depending on the treatments used. Foods containing 3% and 6% banana flour showed the highest growth and food conversion rates, with respective specific growth (SGR) rates of 3.98 and 3.62, as well as conversion rates (CI) of 1.8 and 1.69. Meanwhile, the food with 10% banana flour obtained a SGR of 2.92 and a CI of 2.01, while the control obtained a SGR of 3.3 and CI of 1.7. Thanks to this test, we were able to observe the impact of bananas on the premature development of tilapia. We will continue to study the use of local agri-food byproducts and waste in feeding this fish.